Gelar Perkara dalam Penentuan Tersangka pada Proses Penegakan UU ITE Perspektif Maqāṣid al-syarī‘ah - Perdana, Libria Gita; Hasibuan, Edi Saputra (AL-SULTHANIYAH, 2026)
This study examines the role of case exposure (gelar perkara) in determining suspects in criminal cases related to Information and Electronic Transactions (ITE) through the lens of maqāṣid al-syarī‘ah to achieve justice. Maqāṣid al-syarī‘ah refers to the fundamental objectives of Islamic law, which aim to protect five essential aspects: religion, life, intellect, lineage, and property. This research provides an in-depth analysis of how case exposure influences the fair determination of suspects in the context of ITE criminal offenses. By understanding the principles of maqāṣid al-syarī‘ah, the study seeks to develop a conceptual framework that guides law enforcement in suspect determination, emphasizing universally recognized principles of justice while ensuring that legal processes align with the moral and ethical values upheld in Islam. It is expected that this research will make a significant contribution to promoting justice in handling ITE criminal cases, in harmony with universal principles and the high values of sharia.